The Effect Of Using Interview Steps Techniques To Improve Students Speaking Skills At Tenth Grade Of Sma Negeri 2 Rantau Utara - April Yanti, Sisca; Harahap, Anna Leli; Harahap, Nurhanna; Rusli, Muhammad (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2023)
Interview Step is collaborative learning technique. Interview Step proves the students’ participation. The speaking skills of the students are not good. The students still have difficulty in aspect of fluency and pronunciation in speaking. The research method is quantitative experimental. Next, in this research is test as instrument, test was divided to pre test and post test. To analysis the data, the writer used formulation of analysis product moment. After calculating the data, there is an effect Of Using Three Steps Interview Techniques To Improve Students Speaking Skills At Tenth Grade of SMA Negeri 2 Rantau Utara. It can be seen from t count > t table (2,96> 1,67) with level 0,05. So, the hypothesis was received